A new large-cell superhard carbon allotrope: orthorhombic oC240. (1st December 2020) - Wei, Qun; Zhang, Rui; Wei, Bing; Tong, Wen; Yang, Ruike; Yan, Haiyan; Zhang, Meiguang; Hu, Mingwei; Zhu, Xuanmin; Yao, Ronghui
Abstract : A new carbon allotrope orthorhombic o C240, is proposed by first principles calculation. The unit cell of o C240 is composed of 240 carbon atoms. The calculated elastic constants and phonon spectra confirmed that o C240 is mechanically and dynamically stable under ambient pressure. The calculated hardness is 56.3 GPa. The electronic structure calculations show that o C240 is an indirect band gap semiconductor with the gap of 2.13 eV. GRAPHICAL ABSTRACT: